Determination of production capacity of circulated primordial germ cells (circulated-PGCs) of KUB chicken using lysis buffer ammonium chloride potassium (ACK) - Soni Sopiyana; Iman Supriatna; M. Agus Setiadi; Mohamad Fahrudin (Indonesian Center for Animal Research and Development (ICARD), 2016)
In poultry embryos, primordial germ cells (PGCs) are progenitor cells for gametes, which have unique migration pathway. Primordial germ cells arise from epiblast in germinal crescent and circulate through the bloodstream for a short period of time, then leave blood vessel to migrate toward gonads. The aim of this study was to determine the potential production capacity of circulated-PGCs of KUB chicken at different developmental stages of embryo using a rapid and simple method. Seventy five KUB chicken fertile eggs were divided into five groups and incubated at 38.5 0C with a humidity of 60%. Hatching was set to the embryonic development stage of 14-18. The blood was collected through dorsal aorta using micropipette under microscope. The collected blood was placed in a 1.5 ml eppendorf tube which was previously filled with 100 µl phosphate buffered saline without Ca2+ and Mg2+ (PBS-) mixed with fetal bovine serum (FBS) with a ratio of 90%:10%. The PGCs were purified using lysis buffer ammonium chloride potassium method. The results showed that average production of circulated-PGCs per embryo of KUB chicken were significantly affected by stage of embryonic development (P <0.05). The average production of circulated-PGCs at stage 14, 15, 16, 17, and 18 were 37.9; 53.5; 49.8; 38.3; and 33.5 respectively. The number of circulated-PGCs was not different among stages 14, 17 nor 18. The highest number of circulated-PGCs of KUB chicken was obtained at stage 15, so that the isolation and collection of PGCs through the blood circulation was recommended in stage 15.Key Words: KUB Chicken, PGCs, Embryonic Development Stage, Ammonium Chloride Potassium